Heat acclimation does not attenuate hepcidin elevation after a single session of endurance exercise under hot condition - Sumi, D.; Nagatsuka, H.; Matsuo, K.; Okazaki, K.; Goto, K. (European Journal of Applied Physiology, 2022)
Purpose We sought to determine the effects of heat acclimation on endurance exercise-induced hepcidin elevation under hot conditions.